Numerical Characterization of the Performance of Fluid Pumps Based on a Wankel Geometry. (29th September 2014) - Wan, Stephen; Leong, Jason; Ba, Te; Lim, Arthur; Kang, Chang Wei
Abstract : The performance of fluid pumps based on Wankel-type geometry, taking the shape of a double-lobed limaçon, is characterized. To the authors' knowledge, this is the first time such an attempt has been made. To this end, numerous simulations for three different pump sizes were carried out and the results were understood in terms of the usual scaling coefficients. The results show that such pumps operate as low efficiency (<30%) valveless positive displacements pumps, with pump flow-rate noticeably falling at the onset of internal leakage. Also, for such pumps, the mechanical efficiency varies linearly with the head coefficient, and, within the onset of internal leakage, the capacity coefficient holds steady even across pump efficiency. Simulation of the flow field reveals a structure rich in three-dimensional vortices even in the laminar regime, including Taylor-like counterrotating vortex pairs, pointing towards the utility of these pumps in microfluidic applications. Given the planar geometry of such pumps, their applications as microreactors and micromixers are recommended.